The Role of Counselling in Addressing Substance Abuse Among Nigerian Youth - Esther Ifeoluwa Folorunso (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study used a quantitative research methodology to investigate the role of counseling in addressing substance dependence among young Nigerians. Substance addiction among young people in Nigeria is becoming more common, which is a serious public health and social issue that calls for efficient intervention techniques like counseling. A sample of 300 respondents provided data for the study, which used a cross-sectional survey design. Of these, 286 valid replies were examined. Data was gathered using a structured questionnaire, and the Statistical Package for the Social Sciences (SPSS) was used to analyze the results using both descriptive and inferential statistics. The results showed that peer pressure, socioeconomic difficulties, and environmental variables were the main causes of Nigerian youth's high prevalence of substance misuse. The survey also discovered that there was a discrepancy between awareness and actual use of counseling services, with access to them being moderate. Crucially, the findings showed that counseling significantly reduces substance misuse; that is, more counseling results in less substance use. Regression analysis also revealed that a significant amount of the variation in substance abuse among respondents was explained by counseling. The study also found that stigma, expense, and ignorance are major obstacles to the efficient use of counseling services. Despite their shown efficacy, these factors severely restrict the impact of counseling interventions. Based on the results, the study comes to the conclusion that counseling is an important and successful strategy for dealing with substance misuse among young people in Nigeria, but its effectiveness depends on increased accessibility, social acceptance, and institutional support. In order to lessen stigma and promote help-seeking behavior, the study suggests increasing government support for counseling services, integrating counseling into educational systems, and launching public awareness campaigns. Future research on creative counseling techniques and long-term intervention outcomes is also recommended by the study.